2006
DOI: 10.1037/0735-7036.120.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Olfactory Sensitivity for Putative Human Pheromones in Nonhuman Primates.

Abstract: In humans, the volatile C19-steroids androsta-4,16-dien-3-one (AND) and estra-1,3,5(10),16-tetraen-3-ol (EST) have been shown to modulate autonomic nervous system responses, and to cause hypothalamic activation in a gender-specific manner. Using two conditioning paradigms, the authors here show that pigtail macaques and squirrel monkeys of both sexes were able to detect AND and EST at concentrations in the micromolar and mM range, respectively. Male and female spider monkeys, in contrast, differed markedly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Although these numbers would fit to the superior sensitivity of the mice found here, they fail to explain why human subjects do not perform poorer than the spider monkeys with the alkylpyrazines tested. Previous studies also led to ambiguous findings, with some of them supporting a positive correlation between the relative size of the olfactory bulbs and a species' sensitivity and some of them failing to do so (Laska et al, 2005b(Laska et al, , 2006d. Further studies, including those addressing the possibility that the degree of neural connectivity rather than absolute or relative numbers of neurons involved in sensory processing may be relevant for the sensitivity of olfactory systems (Keverne, 2004), are clearly needed to draw further conclusions.…”
Section: Discussionmentioning
confidence: 84%
“…Although these numbers would fit to the superior sensitivity of the mice found here, they fail to explain why human subjects do not perform poorer than the spider monkeys with the alkylpyrazines tested. Previous studies also led to ambiguous findings, with some of them supporting a positive correlation between the relative size of the olfactory bulbs and a species' sensitivity and some of them failing to do so (Laska et al, 2005b(Laska et al, , 2006d. Further studies, including those addressing the possibility that the degree of neural connectivity rather than absolute or relative numbers of neurons involved in sensory processing may be relevant for the sensitivity of olfactory systems (Keverne, 2004), are clearly needed to draw further conclusions.…”
Section: Discussionmentioning
confidence: 84%
“…It should be mentioned, however, that these studies employed changes in respiration frequency and heart rate, respectively, to determine olfactory detection thresholds, and both methods are known to be less sensitive than operant conditioning procedures (Hastings, 2003). A within-species comparison between the detection threshold values of the present study with those obtained in earlier studies using the same methods and animals but with other classes of odorants such as aliphatic esters (Hernandez Salazar et al, 2003;Laska and Seibt, 2002a), alcohols (Laska and Seibt, 2002b;Laska et al, 2006a), aldehydes (Laska et al, 2003b;Laska et al, 2006a), ketones (Laska et al, 2005a), carboxylic acids , terpenes (Laska et al, 2006c), thiazoles (Laska et al, 2005b), or steroids (Laska et al, 2005c;Laska et al, 2006b) reveals that in all three species of primate at least one of the putrefaction-associated odorants employed here (indol with squirrel monkeys and pigtail macaques, ethanethiol and 3-methyl indol with the spider monkeys) yielded the lowest detection thresholds among the more than 50 odorants tested so far. This finding is in line with reports showing that human subjects are particularly sensitive to thiols and indols (van Gemert, 2003).…”
Section: The Journal Of Experimental Biologymentioning
confidence: 84%
“…However, while the results of Bensafi et al (2003) revealed no effect of EST on physiological arousal, the same authors found EST to affect physiological arousal in a content-dependent way (Bensafi et al, 2004). Exploring the conscious odor perception of AND and EST in an animal model, a gender-specific effect was obtained by Laska et al (2006), who detected olfactory sensitivity to AND in female, but not male, spider monkeys, while responses to the highest concentrations of EST were found in males, but not in female, monkeys. These data also highlight the gender-specific processing of these two pheromone-like compounds in non-human animal models.…”
Section: Neuronal Correlates Of Andmentioning
confidence: 96%